Securitization in Poland as an Innovative Solution in the Capital Markets - Biernacki, Krzysztof (Sekurytyzacja w Polsce jako innowacja na rynku kapitałowym, 2010)
The development of international financial markets depends on financial innovations. For those markets the securitization of assets may be regarded as one of such innovations. Since 1997 some securitization programmes have been executed in Poland too. This study is an attempt to answer, in the light of theories on financial innovation, whether domestic securitization is a new financial instrument. A positive answer to this question may also point to a general trend of the securitization market in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 9-26
Keywords: securitization; capital markets; innovation